KISHI MEKTEP JASTAǴÍ BALALARDÍŃ SHAXS BOLÍP QALIPLESIWI - Elmuratova, A.U.; Babajanova, G.M. (SCIENCE and SOCIETY, 2022)
The article deals with the formation of the personality of young schoolchildren at school and the influence of society on the formation of their personality, moral standards, and the formation of behavioral action.
Keywords: school age; personality; personality and society; behavior; consciousness; logical thinking; emotion